2022
DOI: 10.1021/acs.jmedchem.1c01280
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-Trisubstituted Pyrimidine Derivatives as Type I RET and RET Gatekeeper Mutant Inhibitors with a Novel Kinase Binding Pose

Abstract: Mutations of the rearranged during transfection (RET) kinase are frequently reported in cancer, which make it as an attractive therapeutic target. Herein, we discovered a series of N-trisubstituted pyrimidine derivatives as potent inhibitors for both wild-type (wt) RET and RET V804M , which is a resistant mutant for several FDA-approved inhibitors. The X-ray structure of a representative inhibitor with RET revealed that the compound binds in a unique pose that bifurcates beneath the P-loop and confirmed the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Zhang et al employed an N-trisubstituted pyrimidine scaffold in the design of a novel type I RET inhibitor, compound 21 (CHEMBL5070593), engineered to overcome the V804M gatekeeper mutation . While featuring a chemical scaffold reminiscent of type II kinase inhibitors, compound 21 binds to RET in a distinctive conformation.…”
Section: Ret Inhibitorsmentioning
confidence: 86%
See 2 more Smart Citations
“…Zhang et al employed an N-trisubstituted pyrimidine scaffold in the design of a novel type I RET inhibitor, compound 21 (CHEMBL5070593), engineered to overcome the V804M gatekeeper mutation . While featuring a chemical scaffold reminiscent of type II kinase inhibitors, compound 21 binds to RET in a distinctive conformation.…”
Section: Ret Inhibitorsmentioning
confidence: 86%
“…Meanwhile, the piperonyl moiety binds relatively loosely between the walls of the ATP-binding site, constrained by Leu730/Gly731 of the P-loop and Gly810/Ser811 of the ribose pocket, without significant polar interactions. This unique binding mode appears influenced by peripheral substituents rather than the hinge binder itself, potentially contributing to its 153 While featuring a chemical scaffold reminiscent of type II kinase inhibitors, compound 21 binds to RET in a distinctive conformation. Unlike typical type II inhibitors that induce a DFG-out state to access a back pocket, compound 21 maintains a DFG-in conformation akin to type I inhibitors.…”
Section: Develop New Ret Inhibitors Targeting V804 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…G810C/S/R in solvent-front region (SF), Y806 C/N (in hinge residue) or V738A (in β2 strand) (Subbiah et al 2021a;Solomon et al 2020) were identified. As a result, substantial efforts have been devoted to discover new selective RET inhibitors for combating unsolved clinical needs (Zhang et al 2022b;Moccia et al 2021) and 4 candidates have been advanced into clinical trials at least. Such as TPX-0046 (Phase I/II, NCT04161391) (Drilon et al 2019;Fancelli et al 2021), LOXO-260 (Phase I, NCT05241834) (Kolakowski et al 2021), TAS0953/HM06 (phase I/II, NCT04683250) (Miyazaki et al 2017) and APS03118 with undisclosed structure which were based on the company's announcement (Subbiah et al 2022) will be discussed next.…”
Section: Other Ret Inhibitors In Developmentmentioning
confidence: 99%
“…As part of a continuous effort to discover kinase inhibitors, [85][86][87][88] we recently reported SP-96, a potent Aurora B inhibitor (IC 50 = 0.316 nM). Through NCI60 screening, we found that this compound shows potent growth inhibition of MDA-MB-468, a TNBC cell line.…”
Section: Recent Studies On Aurora Kinase Bmentioning
confidence: 99%